Analisis Buku Teks Pelajaran Bahasa Arab SMA/SMK Muhammadiyah Pada Maharah Al-Kalam Sesuai Standar Common European Framework Of Reference (CEFR) - Salim Saputra; Tulus Musthofa (Lugawiyyat, 2022)
Learning Arabic in SMA/SMK Muhammadiyah aims to develop language competence in the aspects of listening, speaking, reading, and writing. This research is literature research with the object of research is an Arabic textbook for class X SMA/SMK Muhammadiyah by Helmy Fauzi Awaliyah and Fauzi. This study focuses on the speaking competence in the book. Analysis of the data using content analysis techniques with the method of observing data sources, both primary data and secondary data, who wants to explore the question of whether the contents of the book and the material presented are relevant to the correct book standards? What level of Arabic speaking competence is in the book based on the Common European Framework of Reference for Language (CEFR) reference? The results showed that in general, Arabic textbooks had fulfilled the material aspects, linguistic aspects, material presentation aspects, and graphic aspects. Then based on the CEFR standard reference, the textbooks are included at levels A1, A2, and B1.